2019
DOI: 10.1111/ina.12531
|View full text |Cite
|
Sign up to set email alerts
|

Effects of indoor environmental parameters related to building heating, ventilation, and air conditioning systems on patients' medical outcomes: A review of scientific research on hospital buildings

Abstract: The indoor environment of a mechanically ventilated hospital building controls infection rates as well as influences patients’ healing processes and overall medical outcomes. This review covers the scientific research that has assessed patients’ medical outcomes concerning at least one indoor environmental parameter related to building heating, ventilation, and air conditioning (HVAC) systems, such as indoor air temperature, relative humidity, and indoor air ventilation parameters. Research related to the natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(79 citation statements)
references
References 186 publications
2
72
0
2
Order By: Relevance
“…Climate control is also an essential part of critical care, and wide variations in the ICU indoor environment have been demonstrated to adversely affect patient outcomes [ [11] , [12] , [13] ]. With all health care professionals donning full complement personal protective equipment (PPE), a reasonably cool environment is vital.…”
Section: Challenges Faced During the Implementation Stagementioning
confidence: 99%
“…Climate control is also an essential part of critical care, and wide variations in the ICU indoor environment have been demonstrated to adversely affect patient outcomes [ [11] , [12] , [13] ]. With all health care professionals donning full complement personal protective equipment (PPE), a reasonably cool environment is vital.…”
Section: Challenges Faced During the Implementation Stagementioning
confidence: 99%
“…While it is known that the indoor air environment plays a critical role in the health of patients in hospitals and buildings, more stringent air quality standards and standardized monitoring protocols in the hospital setting are needed [1]. Previous studies with portable air purification in the hospital setting have shown the potential to reduce potentially infectious bacteria and mold and have stressed the importance of patients breathing clean air in their local environment [13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…The quality of the air within the hospital can significantly impact the health of individuals within this space [1]. Specifically, the air provides a vehicle for the spread of bacteria, viruses, 1 2 3 4 fungi, and other airborne toxins and can contribute to potentially lethal hospital-acquired infections [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hospital facilities have unique requirements compared to other buildings given that patient outcomes (patient pain levels, lengths of stay, infection rates, patient recovery rates, patient mortality rates) as well as staff outcomes (such as overall workplace safety, infection control metrics, stress levels, and staff sense of well-being), are intricately connected to the built environment of the hospital itself [6][7]. Additionally, indoor air quality and HVAC parameters can impact patient outcomes [7]. Air flow and thermal control can directly relate to patient comfort and recovery and hospital patient satisfaction metrics [8].…”
Section: Introductionmentioning
confidence: 99%